Pengaruh Perbandingan Media Tanam Arang Sekam dan Kompos Daun Bambu (Bambusa Sp) Terhadap Pertumbuhan Semai Tanjung (Mimusops elengi Linn.) - Maria Nona Ertin; Astin E. Mau; Norman P. L. B. Riwu Kaho; Muhamad Soimin (Wana Lestari, 2026)
Tanjung (Mimusops elengi Linn.) belongs to the Sapotaceae family, which grows well at an altitude of less than 800 meters above sea level. This tree is a multipurpose tree that can be utilized, where the wood is known to be durable, hard, strong, suitable for construction such as bridges, boats, ships, floors, and doors. Tanjung does not require high light intensity at the beginning of its growth. The provision of rice husk charcoal and bamboo leaf compost can increase the availability of nutrients including, SiO2 (52%), C (31%), Fe 2O3, K2O, MgO, CaO, MnO, C-organic (18.45%), N (1.07%), P (1.83%), and K (1.48%), %, Ca 0.05%, Mg 0.05%, Fe 421.5%, Cu 1.53%, Zn 4.54%, Mn 46.31% which is high enough so that it has the potential as the main ingredient in soil structure restructuring and plant growth. The method used in this study was a (RAL) with a comparison of the composition of the planting media. The results of the study showed that the provision of rice husk charcoal and bamboo leaf compost had a very significant effect on all parameters and the provision of rice husk charcoal and bamboo leaf compost in the treatment (D2) 2.5 kg soil + 1 kg rice husk charcoal + 1.5 kg bamboo leaf compost, was the best treatment that gave an effect on the increase in plant height (4.060 cm), increase in stem diameter (0.864 cm), increase in the number of leaves (4.800 strands), wet weight (1.030 grams), and dry weight (0.296 grams).